Americans and Macao : Trade, Smuggling, and Diplomacy on the South China Coast - Van Dyke, Paul Arthur (Book collections on Project MUSE., 2012)
The theme of this volume is the American relationship with Macao and its region through trade, politics, and culture, and the focus is mainly on the late eighteenth and nineteenth centuries. The essays address topics such as the role of the China trade in US pacific expansion and exploration, US consuls, smuggling networks, American women's perceptions of China, and missionary and educational work. In all of the encounters, Macao emerges as a central player, adding a new dimension to our understanding of Sino-American relations. -- Publisher's website.